Evapotranspiration measurement and estimation of crop coefficient for native plant species of green roof in the tropics - Chow M.F.; Bakar M.F.A.; Wong J.K.; Ling L. (MDPI AG, 2023)
Crops; Evapotranspiration; Moisture control; Soil moisture; Tropics; Wind; Different substrates; Environmental parameter; Extensive green roofs; Reference evapotranspiration; Soil moisture sensors; Tropical climates; Urban stormwater management; Water retention capacity; Roofs; absorption coefficient; estimation method; evapotranspiration; grass; measurement method; native species; roof; runoff; soil moisture; tropical region; wastewater treatment; Axonopus compressus